Outpatient Psychotherapy Reduces Health-Care Costs: A Study of 22,294 Insurants over 5 Years - Altmann, Uwe; Zimmermann, Anna; Kirchmann, Helmut A.; Kramer, Dietmar; Fembacher, Andrea; Bruckmayer, Ellen; Pfaffinger, Irmgard; von Heymann, Fritz; Auch, Emma; Steyer, Rolf; Strauss, Bernhard M. (Frontiers in Psychiatry, 2016)
Background: The project “Quality Assurance in Ambulatory Psychotherapy in Bavaria” (QS-PSY-BAY) focuses on the quality assurance of outpatient psychotherapy (OPT) in Germany in terms of symptom reduction and cost reduction under naturalistic conditions. In this study we examined the effectiveness of psychotherapy in terms of pre-post cost reduction. Method: The health care costs of N = 22,294 insurants over a five year period were examined in a naturalistic longitudinal design. Six participating health insurance funds provided data on costs related to inpatient treatment, outpatient treatment, drugs, and hospitalization and work disability days. Results: We found that the average annual total costs for inpatient and outpatient treatments as well as drug costs and work disability days increased from the 2nd to the 1st year before OPT. Besides a large and significant reduction of work disability days (41.8%), hospitalization days (27.4%), and inpatient costs (21.5%) from the 1st year before versus the 1st year following OPT, we found evidence for long-term effects: the number of work disability days in the 2nd year after OPT was lower (23.8%), and drug costs were higher than in the 2nd year before OPT (41.5%). Conclusions: We conclude that OPT as a part of the health insurance system, is an investment which can pay off in the future especially in terms of lower inpatient costs and work disability.